Perovskite photodetector for high speed and secure Li-Fi wireless data transmission - Akmal Saiful, Muhammad Alauddin Nafis; Mohd Ghazali, Mohd Ifwat; Abdullah, Shahino Mah (Universiti Teknologi MARA, Negeri Sembilan, 2025)
In the contemporary digital environment, the shortcomings of traditional radio-frequency wireless communication, like bandwidth congestion, energy inefficiency, and susceptibility to security breaches, have become increasingly evident. Light Fidelity (Li-Fi) is a viable option, utilising visible light to convey data at exceptionally high velocities while mitigating numerous urgent obstacles. This research centres on the creation of a high-speed and secure Li-Fi system, specifically highlighting the utilisation of a perovskite-based photodetector to improve performance. Perovskite materials have garnered interest in recent years due to their remarkable optoelectronic characteristics, including elevated absorption coefficients, adjustable bandgaps, and rapid photo response times. These attributes render them exemplary choices for photodetectors in optical communication systems. This study involves the fabrication of a perovskite photodetector, which is incorporated into a prototype Li-Fi system aimed at showcasing efficient, real-time data transmission utilising visible light sources, including LEDs or laser diodes. The proposed Li-Fi system utilises the underutilised visible light spectrum, which is around 10,000 times wider than the radio spectrum, facilitating ultra-fast data transfer rates and mitigating spectrum congestion. The incorporation of perovskite photodetectors improves the system's responsiveness and energy efficiency, rendering it appropriate for contemporary smart city infrastructure and advanced educational settings. Moreover, Li-Fi has inherent benefits regarding data security, as light is unable to permeate opaque materials such as walls, thereby limiting signal access to certain physical areas. This study showcases a small-scale demonstration of a perovskite-integrated Li-Fi communication system, emphasising its potential to transform wireless data transmission through enhanced speed, security, and sustainability. As Li-Fi technology advances and incorporates sophisticated photodetector materials such as perovskites, it heralds a new epoch of high-performance, environmentally sustainable wireless communication networks.